Double-sided detector for electron beam alignment and measurement of back-streaming electrons in ExtendedEBIS at BNL. Issue 1 (1st April 2022) - Ikeda, Shunsuke; Beebe, Edward; Kanesue, Takeshi; Kondrashev, Sergey; Okamura, Masahiro
Abstract: We developed an electron beam detector installed between the superconducting solenoids in ExtentedEBIS. The detector is two-sided. Each side has 4 quadrant plates with an aperture slightly larger than the electron beam radius. The gun-side is for alignment of primary electron beam. The collector side detector is to measure the electrons back-streaming from the collector or the downstream electrodes to the cathode. It is important to understand how the back-streaming electrons behave and how to control it. The detector was designed with considerations of heat load. The influence on the electric potential distribution was investigated. A detector test showed that the back-streaming electrons were affected by the external electromagnetic fields and the space charge of the primary electron beam. It was proved that the behaviour of the electrons can be observed by this detector.